PSVIII-17 In vitro and in vivo investigations of effects of natural phytogenic compounds on muscle cell gene expressions and growth performance and carcass composition of finishing pigs. (5th December 2019) - Kim, Y-J; Kim, J-H; Kim, J-W; Kim, S-H; Eun, J -S; Hong, S-M
Abstract: For lean meat production in swine industry, some synthetic compounds have been applied as feed additives in finishing swine feeds. However, this practice raises public concern due to potential imbalance of innate hormones coupled with a possible residue of the synthetic compounds in meat products after ingestion. In this study, we investigated natural phytogenic compounds (NPC) from fruit peel consisted of mainly ursolic and maslinic acids to enhance muscle development but decrease fat deposition in swine. To test effects on cell line, NPC was treated in the porcine primary cell line obtained from muscle tissue of piglets at approximately 6.5 kg of body weight and NIH-3T3-L1 cell line from mouse adipose tissue cell (Experiment 1). In the porcine primary cell line, immunofluorescence measurement indicated that myogenin expression increased at 20%, while the genes responsible for muscle development increased RNA abundance in MyoD at 20%, Mrf4 at 31%, PAX3 at 19%, and PAX7 at 16% observed in myotube development from myoblast when treated with NPC (P < 0.05). In NIH-3T3L1 cell, NPC treatment increased suppression on lipid accumulation at 40% (P < 0.05). In a follow-up in vivo investigation in a completely randomized design (Experiment 2), the same NPC tested in Experiment 1 at 0.53% dry matter (DM) did not affect intake of DM, whereas it tended to increase average daily gain compared with control without NPC supplementation (1.03 vs. 0.99; P = 0.08), leading to a tendency to increase gain-to-feed ratio (0.338 vs. 0.316; P = 0.12). While NPC supplementation did not influence hot carcass weight, animals treated with NPC decreased backfat thickness compared to those fed control (23.5 vs. 24.8 mm; P < 0.01). In summary, NPC from fruit improved growth performance and carcass trait due to their impacts on muscle cell development and fat deposition.